Kelembagaan Masyarakat Sebagai Media Partisipasi Masyarakat Berbasis Komunitas Cerdas dalam Pengelolaan Hutan Mangrove di Kelurahan Mangunharjo - Nabilah Aafiyah; Mussadun Mussadun (Teknik PWK (Perencanaan Wilayah Kota), 2022)
Mangrove forest management is inseparable from the role of the local community as well as the role of policy makers and other parties who have contributed to creating sustainable mangrove forests. The existence of community institutions can be able to restore and develop the potential of mangrove forests to be a source of flood and tidal control to increase the living standards of coastal communities. In line with the development of the Smart City Semarang Masterplan, the mangrove management community institution makes it possible to tackle the problem of increasing the extent of flood and tidal inundation in the city of Semarang by optimizing the preservation of mangrove forests based on the dimensions of a smart society as it contains a smart community program. Therefore in this article used the method of participation analysis, rank spearman analysis and institutional analysis is used to determine the suitability of the role of community institutions as a media for community-based smart community participation in mangrove forest management. The results of the analysis conducted is through participation analysis obtained participation value of 52.87 where the respondents have a broad understanding of the implementation of mangrove forest management activities and have a sense of responsibility and are actively involved in mangrove forest management in Mangunharjo Village. Supported by the results of the spearman rank correlation analysis showed a strong correlation with mangrove management participation in Mangunharjo Village, specifically the experience of participating in mangrove management programs with a correlation coefficient value of 0.641. And the results of the institutional analysis have an average score of 59.41 which indicates that there are community institutions that have played a role as a media for community-based smart community participation in mangrove forest management in Mangunharjo Village according to the smart community indicator.